In search of the bloc bourgeois - Bruno Amable (Revue de la Régulation)
This paper proposes an analysis of the social bloc that could support the political strategy of a radical change of the socio-economic model in France. This social bloc, the bloc bourgeois, would gather the affluent and educated groups of the traditional left and right social blocs that had structured political competition during the Fifth Republic. The analysis is based on an empirical study of the policy demands of the electorate based on the French electoral survey 2012. A latent class model leads to a partition of the French electorate in eighteen clusters. This analysis sheds light on the composition of the respective social bases of the left and the right as well as on the possibility of existence of the bloc bourgeois. The paper also contributes to explaining the reasons for François Hollande’s failure as well as the difficulties of the current Emmanuel Macron presidency.